The Republican Oncology Dispensary's experience in treating malignant trophoblastic tumors: ways of improvement - Z. A. Gasanbekova; S. A. Aliev; L. A. Meshcheryakova; V. V. Kuznetsov (ABV-press, 2014)
This paper covers the topical problems of the diagnosis, treatment, and monitoring of trophoblastic tumors at regional cancer centers. Using as an example the Department of Gynecology, N.N. Blokhin Russian Cancer Research Center, Russian Academy of Medical Sciences, our country's leading institution dealing with the problems of trophoblastic tumors, the authors show that it is necessary to introduce interna- tional standardized chemotherapy regimens and organ-sparing operations, which are able not only to cure young women, but also to preserve their reproductive function, into the practice of specialized facilities.